2021
DOI: 10.2147/amep.s298645
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Authorship Practices Among Health Science Students: A Cross-Sectional Study

Abstract: Background The International Committee of Medical Journal Editors has published clear guidelines on the authorship of scientific papers. It is the research team’s responsibility to review and ensure those guidelines are met. Authorship ethics and practices have been examined among healthcare professionals or among particular health science students such as medical students. However, there is limited evidence to assess the knowledge of authorship roles and practices among health science students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A study conducted by Badreldin et al in Saudi Arabia reported insufficient knowledge regarding authorship guidelines and unethical practices involved in scientific publication among health science students and recommended universities and research centers to measures to increase awareness regarding authorship guidelines [ 19 ]. Moreover, in Saudi Arabia, most of the researchers and health care providers are non-native English speakers, who tend to have difficulty writing in a clear, concise, and credible manner to meet journal requirements [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Badreldin et al in Saudi Arabia reported insufficient knowledge regarding authorship guidelines and unethical practices involved in scientific publication among health science students and recommended universities and research centers to measures to increase awareness regarding authorship guidelines [ 19 ]. Moreover, in Saudi Arabia, most of the researchers and health care providers are non-native English speakers, who tend to have difficulty writing in a clear, concise, and credible manner to meet journal requirements [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, based on limited published surveys of graduate students (Badreldin et al, 2021; Karani et al, 2013), it’s clear that instruction on authorship, such as teaching the standard criteria that qualify someone as an author of different types of written products (e.g., data analyses vs. policy briefs or persuasive essays) and how to engage with co-authors, is not uniformly covered. Learning disciplinary conventions and practices around authorship within different public health fields and across professional settings is essential to students as they apply these practices in their own writing and critically evaluate written documents.…”
mentioning
confidence: 99%
“…Research societies can play a constructive role in this regard by promoting research and publication ethics among young researchers. Educational institutions and seniors can educate and train their students and incorporate research ethics in their curricula to follow the authorship ethos [ 10 ].…”
mentioning
confidence: 99%